Recurrent Rheumatic Fever - Patriotika Ismail; Cecep Suryani Sobur; Cyntia Olivia (Indonesian Rheumatology Association, 2019)
Rheumatic fever (RF) may often be encountered in developing country including in Indonesia. RF is autoimmune disease resulted from Group-A Streptococcus upper respiratory tract infection. RF diagnostic criteria underwent some changes since it was first arranged. Patients with RF episode history have a higher risk to experience recurrence following Group-A Streptococcus pharyngeal infection and need long-term antibiotic prophylaxis to prevent severe disease and RHD. Here we present a case of patient who has RF and RHD history since the age of 10 years old. This case is reported to show recurrent RF management and prophylaxis treatment that can be done next to prevent recurrence of RF in the future.